AL-‘ALAAQAH BAINA ISTII’AAB AN-NAHWU WANATIIJAH TA’ALIM MAHARAH AL-KITAABAH LIDAA THULLAAB AL-MADRASAH AL-MUTAWASITHAH BI MA’HAD UMMUL QURO AL-ISLAMI BOGOR - Nurul Fahmi (SHAWTUL ARAB, 2023)
Based on the analysis of the previous data that was explained in the fourth chapter, which indicates the results of the hypothesis test in which the t-test is used, the researcher presents the conclusion that there is a relationship between grammar comprehension and the result of learning writing skill among middle school students Umm al-Qura Islamic Bogor. And depending on the benefit test, as shown in the previous book, the coefficient of the relationship between the comprehension of grammar and the result of learning the skill of writing, so the research hypothesis that expresses that there is a positive relationship between the comprehension of grammar and the result of learning the writing skill is true. The coefficient of computer torque is the square of the coefficient of the relationship between the comprehension of grammar and the result of learning the skill of writing. It is ²r_y1 = (0.910)² = 0.8281. The value of the t-test (19.12) is greater than the t-table at the significance level (0.05) which is (1.98) and the degree of freedom (dk = 76). And from the t table, the level of significance (0.01) is (2.62) and the degree of freedom (dk = 76). Eduction: The relationship between the comprehension of grammar and the result of learning the writing skill of students in Umm Al-Qura Islamic Intermediate School, Bogor, very beneficial